Madam C.J. Walker : the making of an American icon - Ball, Erica L., 1971- (Library of African-American biography., 2021)
Madam C. J. Walker is reputed to be America's first self-made woman millionaire. Born to former slaves in the Louisiana Delta in the aftermath of the Civil War, married at fourteen, and widowed at twenty, Walker spent the first decades of her life as a laundress. By the time of her death in 1919, however, Walker had refashioned herself into one of the most famous African American figures in the nation: the owner and president of a hair-care empire and a philanthropist wealthy enough to own a country estate near the Rockefellers in the prestigious New York town of Irvington-on-Hudson. -- adapted from back of book